Increased Transfollicular Absorption of Liposomal Sepia Melanin Enhanced by Dilatation of Follicular Infundibulum by Microneedling - Gabriel Serrano; Patricia Almudéver; Juan M Serrano; Julio Cortijo; Carmen Faus; Magda Reyes; Inmaculada Expósito; Ana Torrens; Fernando Millán (Achievements and Challenges of Medicine and Medical Science Vol. 1, 2024)
The skin represents an important barrier to the penetration of exogenous substances into the body and also a potential route for the transport of functional active principles into the skin and hair. Encapsulation of chemicals in liposomes and microneedling are currently used techniques to enhance the penetration of several substances through skin and hair. The objective of the study is to study the transfollicular penetration of sepia melanin encapsulated in nanoliposomes (Melaser solution, Sesderma, Valencia, Spain) applied with a new microneedling electrical device on an ex vivo model of human skin. In this study, a liposomal melanin–fluorescein compound to an ex vivo model of human skin, using a new electrical microneedling device (Nanopore turbo roller), has been applied. The product was applied by hand massage (A) or with the assistance of the electrical roller for 2 minutes (B). An additional test was performed free of product and with only the E-roller (C). Histological changes and product absorption were evaluated by optical and fluorescent microscopy 60 and 90 minutes after the treatment. The clinical study protocol was prepared, reviewed, and approved by the General Hospital of Valencia Ethics Committee. Site B showed larger deposits of melanin–fluorescein at superficial and deep levels of hair structures in comparison to site A. Light, epidermal deposits of the melanin–fluorescein complex were also observed. Sites B and C showed a significant widening (47%) of the follicular infundibulum which could explain the increased penetration of the formulation. Microneedling also removed the scales and sebum residues in the neighborhood of the infundibulum. Targeting hair follicles with melanin may be useful to dye poorly pigmented hairs, improving laser hair removal. The procedure accelerates the delivery of melanin into hair structures allowing an even absorption, larger pigment deposits, and deeper penetration of the formulation into the hair. The study recommended that the procedure will significantly reduce the application time of the melanin solution from weeks to minutes, as well as increase the amount of product deposited in the deeper hair structures, reducing the cost of the hair-removal procedure.